THE INFLATION AND POVERTY IN INDONESIA: CONSEQUENCE OF USURY? - Azwar Iskandar; Bayu Taufiq Possumah; Khaerul Aqbar (Jurnal Ilmiah Al-Syir'ah, 2019)
This research was conducted to analyze the influence and correlation of interest rates as one form of the implementation of usury practices on inflation and poverty in Indonesia. This study uses secondary data from the publication of the Central Statistics Agency (BPS) and Bank Indonesia for the period 2005-2018. This study uses Simple Linear Regression Analysis Techniques and Pearson Correlation Techniques. The results showed that interest rates as one form of the implementation of usury practices had an effect and had a positive and significant correlation to inflation in Indonesia. The practice of ribawi actually will bring a negative impact on the economy of the people in Indonesia in the form of an increase in the level of inflation in society. Measures of monetary policy intervention in maintaining price stability and inflation in society have not shown a positive impact. Also, the results of the study showed that interest rate policy also had a positive influence and correlation on the increase in the poverty depth index. That is, when interest rates are set to rise, the poverty depth index in the community also tends to go up or get worse. The findings of this study reinforce the legitimacy of the word of Allah Subhanahu Wa Ta'ala in the Qur'an and the Hadith related to the prohibition of usury practices that can lead to injustice, wrongdoing, and economic destruction of the people.